Twelfth night [Večer trojkráľový anglicky] - Shakespeare, William, 1564-1616; Shakespeare, William, 1564-1616.; Macaw Books (Leicester : Sweet Cherry Publishing, 2020)
Twelfth Night by William Shakespeare is a delightful comic love story. The play begins with a shipwreck, during which Viola, a young aristocratic-born woman, is separated from her identical twin brother, Sebastian, and is swept onto the shores of the Kingdom of Illyria. Thus begins this entertaining tale of mistaken identities and thwarted love.
A short narrative version of the play has been suitably adapted to help to introduce the play to young readers.
Keywords: Shipwreck survival -- Pictorial works -- Juvenile fiction; Brothers and sisters -- Pictorial works -- Juvenile fiction; Mistaken identity -- Pictorial works -- Juvenile fiction; Illyria -- Pictorial works -- Juvenile fiction; Children's stories -- Pictorial works; čítam si sám (7+); cudzojazyčná literatúra